Vascular normalization: reshaping the tumor microenvironment and augmenting antitumor immunity for ovarian cancer - Yu, Ping; Wang, Yaru; Yuan, Dahai; Sun, Yunqin; Qin, Shuang; Li, Tianye (Frontiers in Immunology, 2023)
Ovarian cancer remains a challenging disease with limited treatment options and poor prognosis. The tumor microenvironment (TME) plays a crucial role in tumor growth, progression, and therapy response. One characteristic feature of the TME is the abnormal tumor vasculature, which is associated with inadequate blood perfusion, hypoxia, and immune evasion. Vascular normalization, a therapeutic strategy aiming to rectify the abnormal tumor vasculature, has emerged as a promising approach to reshape the TME, enhance antitumor immunity, and synergize with immunotherapy in ovarian cancer.This review paper provides a comprehensive overview of vascular normalization and its potential implications in ovarian cancer. In this review, we summarize the intricate interplay between antiangiogenesis and immune modulation, as well as ICI combined with anti-angiogenesis therapy in ovarian cancer. The compelling evidence discussed in this review contributes to the growing body of knowledge supporting the utilization of combination therapy as a promising treatment paradigm for ovarian cancer, paving the way for further clinical development and optimization of this therapeutic approach.